Can Supplementation with Vitamin D Modify Thyroid Autoantibodies (Anti-TPO Ab, Anti-Tg Ab) and Thyroid Profile (T3, T4, TSH) in Hashimoto’s Thyroiditis? A Double Blind, Randomized Clinical Trial - Chahardoli, Reza; Saboor-Yaraghi, Ali-Akbar; Amouzegar, Atieh; Khalili, Davood; Vakili, Azita Zadeh; Azizi, Fereidoun (Hormone and Metabolic Research, 2019)
Hashimoto’s thyroiditis (HT) is the most prevalent autoimmune disorder characterized by the destruction of thyroid cells caused by leukocytes and antibody-mediated immune processes accompanied by hypothyroidism. In recent years, evidence has emerged pointing to various roles for vitamin D, including, proliferation and differentiation of normal and cancer cells, cardiovascular function, and immunomodulation. Vitamin D deficiency has been especially demonstrated in HT patients. The aim of this study was to investigate the effect of vitamin D on circulating thyroid autoantibodies and thyroid hormones profile (T4, T3, and TSH) in females with HT. Forty-two women with HT disease were enrolled in this randomized clinical trial study and divided into vitamin D and placebo groups. Patients in the vitamin D and placebo groups received 50 000 IU vitamin D and placebo pearls, weekly for 3 months, respectively. The serum levels of 25-hydroxy vitamin D [25(OH) D], Ca++ion, anti-thyroperoxidase antibody (anti-TPO Ab), anti-thyroglobulin antibody (anti-Tg Ab), T4, T3, and TSH were measured at the baseline and at the end of the study using enzyme-linked immunosorbent assays. The results of this study showed a significant reduction of anti-Tg Ab and TSH hormone in the Vitamin D group compared to the start of the study; however, there was a no significant reduction of anti-TPO Ab in the Vitamin D group compared to the placebo group (p=0.08). No significant changes were observed in the serum levels of T3 and T4 hormones. Therefore, vitamin D supplementation can be helpful for alleviation of the disease activity in HT patients; however, further well controlled, large, longitudinal studies are needed to determine whether it can be introduced in clinical practice.
Keywords: CD4+T cell; Hashimoto's thyroiditis; vitamin D supplementation; 1,25(OH)2D3